Ex Libris Andrzeja Ryszkiewicza / [Maria Hiszpańska Neumann]. - Hiszpańska-Neumann, Maria (1917-1980) (1955)
Przedstawia siedzącą, nagą, długowłosą kobietę. Na tarczy napis: Ex Libris Andrzeja Ryszkiewicza.